Literature Riview: Integrasi Sistem Informasi Kepegawaian Terhadap Efisiensi Penganggaran Biaya SDM di Instansi Pemerintah - Lailatul Rushaj; Fajar Syaiful Akbar (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2025)
This study aims to analyze the impact of integrating the Human Resource Information System (HRIS) on the efficiency of human resource (HR) budgeting in government institutions and regional owned enterprises (BUMD). Using a Systematic Literature Review (SLR) appoarch. This research synthesizes findings from six nationally accredited journals (2018-2024), complemented by practical observations during an intership at Perumda Air Minum Surya Sembada Kota Surabaya. This results reveal that HRIS implementation significantly reduces operational cost up to 90% and enhances the accuracy of employee data such as attendance, overtime, and allowances. Furthermore, the system accelerates financial reporting, strengthens transparency, and support real time decision making. The sudy concludes the HRIS integration plays a strategic role in improving budgeting efficiency and accountability in public sector financial manajement. Practically, this research emphasizes the importance of HR digitalization in supporting effective and transparent HR budgeting.